Respuesta :

Factoring a polynomial involves writing the polynomial in a simpler form

The factored form of the polynomial is: [tex]y = (x + 3)(x + 2)(x - 1)(x -3)[/tex]

How to factor the polynomial

From the graph, the zeros of the graph are:

x = -3

x = -2

x = 1

x = 3

Equate the above equations to 0

x + 3 = 0

x + 2 = 0

x - 1 = 0

x - 3 = 0

Multiply the equations

[tex](x + 3)(x + 2)(x - 1)(x -3) = 0 *0*0*0[/tex]

This gives

[tex](x + 3)(x + 2)(x - 1)(x -3) = 0[/tex]

Express as a function

[tex]y = (x + 3)(x + 2)(x - 1)(x -3)[/tex]

Hence, the factored form of the polynomial is:

[tex]y = (x + 3)(x + 2)(x - 1)(x -3)[/tex]

Read more about polynomials at:

https://brainly.com/question/4142886